Estratégias de competição da Igreja Metodista no mercado religioso nordestino - Marinho, Ricardo Aurelio Madeira (2016)
In northeast of Brazil, the Methodist Church, as an evangelical mission church, entered the Brazilian religious field through evangelism, either performed by itinerant missionaries, in its beginning, or by proselytism in the communities where it was present through social or educational works, after its consolidation in the country. However, since the 1990s, with significant changes in the Brazilian religious field, notably the growth of neopentecostal churches, the Methodist Church saw its number of members stagnate and, in some cases, even decline. This rapid growth of neopentecostal churches transformed the Brazilian religious field in a way that promoted changes in forces and resulted in greater competition among religious institutions, which led some religious leaders to a redefinition of their competitive models and strategies. In the case of the Methodist Church in northeastern lands, it is known that some strategies were aimed at a numerical increase of members and, at least, at the maintenance of its space in the religious field. Among the researched strategies are: a) the use of the media; b) the use of marketing and management concepts; c) specialization of religious goods and services; d) changes in liturgies and worship spaces; e) emphasis on tithing. This study aims to investigate the causes and consequences of incorporating competition strategies – business or neopentecostal strategies – in order to maintain the space of the Methodist Church in the religious field, in a church whose doctrines and theological bases are consolidated and point to the movement of the Protestant Reformation.